Prediction of high bell stages of necrotizing enterocolitis using a mathematic formula for risk determination - Diez, Sonja; Bell, Lea Emilia; Moosmann, Julia; Weiß, Christel; Müller, Hanna; Besendörfer, Manuel (Children, 2022)
Necrotizing enterocolitis (NEC) continues to cause high morbidity and mortality. Identifying early predictors for severe NEC is essential to improve therapy and optimize timing for surgical intervention. We present a retrospective study of patients with NEC, treated between 2010 and 2020, trying to identify factors influencing the severity of NEC. Within the study period, 88 affected infants with NEC or NEC-like symptoms are analyzed. A multiple logistic regression analysis reveals the following three independent predictors for NEC in Bell stage III: red blood cell transfusion (p = 0.027 with odds ratio (OR) = 3.298), sonographic findings (p = 0.037; OR = 6.496 for patients with positive vs. patients without pathological findings) and cardiac anatomy (p = 0.015; OR = 1.922 for patients with patent ductus arteriosus (PDA) vs. patients with congenital heart disease (CHD); OR = 5.478/OR = 2.850 for patients with CHD/PDA vs. patients without cardiac disease). Results are summarized in a clinical score for daily application in clinical routine. The score is easy to apply and combines clinically established parameters, helping to determine the timing of surgical intervention.
Gesehen am 19.02.2024